Volatile profile of two monovarietal white wines under different antioxidant environments during storage in bottle - Santos, Cátia V. Almeida (2022)
The authors acknowledge Rui Bicho from Laboratório de Enologia da Universidade de Évora for technical assistance. This research was also anchored by the RESOLUTION LAB, an infrastructure at NOVA School of Science and Technology.